Annoying noise: effect of anthropogenic underwater noise on the movement and feeding performance in the red cherry shrimp, Neocaridina davidi - Azarm-Karnagh, Sasan; López Greco, Laura; Shafiei Sabet, Saeed (Frontiers in Ecology and Evolution, 2023)
Anthropogenic noise in marine and freshwater environments has increased dramatically, with a range of negative impacts and detrimental consequences on many aquatic animals across taxa. Benthic organisms, including many invertebrates, can sense underwater sounds, yet the responses they trigger in these organisms have received little attention. We conducted two laboratory-based experiments to investigate the effect of underwater sound playback on the movement behavior and feeding performance of the red cherry shrimp Neocaridina davidi as a model of freshwater decapod. Movement speed decreased significantly upon opening the divider in both the sound and control treatments. However, there were no significant sound-dependent changes overall between the control and sound treatments. The spatial distribution of shrimp in response to the sound treatment showed significant changes; shrimp spent more time at the farthest one-third position from the sound source. Feeding latency (latency to find food) also increased in the sound treatment compared to the control. Moreover, in terms of the number of successes and failures in finding the food source in the control treatment, significantly more shrimp succeeded in finding the food source. The number of revisits to the food source decreased in the sound treatment compared to control and more shrimp were significantly distracted in the sound treatment. Our study highlights the potential for human-made sound to impact on crustacean activity. Thus, they are prone to the impacts of anthropogenic noise, causing negative impacts on their movement-swimming activities, and feeding behavior. Behavioral changes observed, namely altered feeding and locomotory behavior may have wider-reaching negative effects, including detrimental impacts on animal fitness.